Identification of Types and Weight of Marine Debris in Each Season at Ancol Gen Beach, Pesawahan, Teluk Betung Selatan, Bandar Lampung - Kurnia, Arda; Maharani, Henni Wijayanti; Delis, Putu Cinthia (Jurnal Ilmiah PLATAX, 2024)
The Ancol Gen Beach is one of the beaches located in the waters of Lampung Bay, offering a variety of activities in the surrounding aquatic environment. These activities have led to an increase in pollution, particularly in the form of marine debris. The distribution of non-submerged marine debris tends to drift and ultimately ends up along the shoreline. This research was conducted from December 2021 to June 2022 at Ancol Gen Beach, Pesawahan, Teluk Betung Selatan, Bandar Lampung. The study aimed to classify and identify the types and weights of marine debris most commonly found at Ancol Gen Beach. Sampling of marine debris was carried out using the line transect method spanning the coastline. The research results revealed that the dominant type of marine debris was single-use plastic, followed by recyclable plastics, textiles, rubber, paper, glass, wood, metal, and hazardous waste (B3). The highest density of marine debris occurred during the rainy season, with a count of 50,020 pcs/m² and a weight of 160,525 g/m². In contrast, the lowest density of marine debris was observed during the dry season, with 15,450 pcs/m² and a weight of 53,250 g/m². The accumulation of macro marine debris along Ancol Gen Beach is suspected to be transported by surface currents and river flows in the vicinity of the shoreline. Keywords: Ancol Gen, Macro-sized, Marine debris, and Seasson. Abstrak Pantai Ancol Gen merupakan salah satu pantai yang berada di perairan Teluk Lampung yang memiliki beragam aktivitas di sekitar perairan tersebut. Aktivitas-aktivitas yang ada menyebabkan peningkatan pencemaran salah satunya berupa sampah laut. Distribusi sampah laut yang tidak tenggelam ke dasar perairan akan hanyut dan berakhir di sepanjang pantai. Penelitian ini dilaksanakan pada bulan Desember 2021- Juni 2022 dan bertempat di Pantai Ancol Gen, Pesawahan, Teluk Betung Selatan, Bandar Lampung. Penelitian bertujuan untuk mengklasifikasi dan mengidentifikasi jenis-jenis serta berat sampah laut yang paling banyak ditemukan di Pantai Ancol Gen. Pengambilan sampel sampah laut menggunakan metode line transek yang membentang sepanjang pantai. Hasil penelitian menunjukkan bahwa jenis sampah laut didominasi oleh sampah jenis plastik sekali pakai, kemudian diikuti oleh sampah plastik daur ulang, tekstil, karet, kertas, kaca, kayu, logam, dan sampah B3. Kepadatan jumlah sampah laut paling tinggi berada di musim hujan sebanyak 50.020 pcs/ m² dan berat sampah laut sebesar 160.525 g/m², sedangkan kepadatan jumlah sampah laut terendah di musim kemarau sebanyak 15.450 pcs/m² dan berat sampah laut sebesar 53.250 g/m². Akumulasi sampah laut makro yang tersebar di sepanjang Pantai Ancol Gen diduga terbawa oleh arus permukaan laut dan aliran sungai yang berada di sekitar pantai tersebut. Kata Kunci : sampah laut, makro, musim, pantai Ancol Gen.